2011
DOI: 10.1192/pb.bp.110.029579
|View full text |Cite
|
Sign up to set email alerts
|

Experience of stigma by people with schizophrenia compared with people with depression or malignancies

Abstract: Aims and methodTo compare the frequency of experiences of stigma reported by people with schizophrenia and by people with other health problems (depression and malignancies). The Stigma section of the Consumer Experiences of Stigma Questionnaire (CESQ) was administered to 153 people with schizophrenia, 106 people with depression and 85 people with malignancies.ResultsUsing multiple regression analysis we showed that after controlling for the differences in the participants' background characteristics, people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Chung and Wong (2004) found that secrecy was the most common mechanism of coping with stigma among patients with mental health problems. In a study of 153 out-patients with schizophrenia in Poland, Switaj et al (2011) reported that 83 per cent of the respondents concealed their illness. In the multi-country INDIGO study, 72 per cent reported the need to conceal their diagnosis, while three out of every four respondents in the French INDIGO study (Daumerie et al, 2012) concealed their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chung and Wong (2004) found that secrecy was the most common mechanism of coping with stigma among patients with mental health problems. In a study of 153 out-patients with schizophrenia in Poland, Switaj et al (2011) reported that 83 per cent of the respondents concealed their illness. In the multi-country INDIGO study, 72 per cent reported the need to conceal their diagnosis, while three out of every four respondents in the French INDIGO study (Daumerie et al, 2012) concealed their diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Experience of stigma or discrimination evokes negative emotional reaction or distress and predisposes to low self-esteem (Wahl, 1999;Link et al, 2001). It also negatively impacts on social relatedness (Perlick et al, 2001), psychosocial functioning (Ertugrul and Ulug, 2004) and quality of life (Rosenfield, 1997;Switaj et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These 20 studies (19.8%) found significant effects for age in perceived and experienced MIS scores. However, the direction of such effects is unclear, as some studies pointed out higher stigma scores among younger samples (Sarkin et al, 2014;Switaj et al, 2011;Zoppei et al, 2014;Ho et al, 2015), while others did so for elderly ones (Park et al, 2015;Vidojevic et al, 2015). Only four of the studies that included elderly participants did not control for or did not report the data related to possible age differences in their samples.…”
Section: Age Differencesmentioning
confidence: 99%
“…Therefore, most of the works considered here failed to show diagnostic effects. In this perspective, it is possible that other variables, such as symptoms severity, present more impact on perceived and experienced MIS scores than the diagnostic (Livingston & Boyd, 2010;Switaj et al, 2011).…”
Section: Mental Illness Stigma In Adultsmentioning
confidence: 99%
“…Although stigma is apparent across a plenitude of minorities and disabilities, mental illness is subject to an exceptional amount of stigma (Hinshaw, 2007;Świtaj et al, 2011;World Health Organization, 1998). According to Hinshaw and Stier (2008) a label of mental illness promotes rejection and suboptimal social interactions, which, to a degree, are unrelated to the actual attributes of those that experience stigma.…”
mentioning
confidence: 99%